egypt privatisation and beyond meeting the challenges of the 21 st century / Philip Moore. - Moore, Philip (Euromoney Publications, 1997)
This item will be dispatched to UK addresses via second class post within 2 working days of receipt of your order. Standard UK delivery is £3.95 per order, so you're only charged once no matter how many items you have in your basket. Any additional courier charges will be applied at checkout as they vary depending on delivery address.